Actor-landscapes as visual canvas for identifying, representing, and aligning stakeholders - Quitzau, Maj-Britt; Hoffmann, Birgitte (Frontiers in Built Environment, 2023)
Tools applied by water professionals in climate adaptation projects tend to have a technical focus and a superficial stakeholder approach. Development of integrative and synergetic solutions require more delicate and transformative forms of stakeholder engagement. Through an action research process, this article explores how a visual canvas for stakeholder engagement can support water professionals in identifying, representing, and aligning stakeholders in development of integrative and synergetic climate adaptation solutions. The visual canvas is developed in the form of 'Actor-Landscapes', and presents a practical tool for engaging stakeholders inspired by Actor-Network Theory. Actor-Landscapes proved to especially support water professionals in four key challenges in their transformative approach to stakeholder engagement: 1) to recognize stakeholders more broadly and deeply, 2) to organize and present data about key stakeholders and the landscape in which these are anchored, 3) to prioritize which stakeholders to enhance based on alignment considerations, and 4) to legitimize mapped stakeholder perspectives through direct dialogue and engagement. The article concludes that Actor-Landscapes have interesting boundary object abilities supporting water professionals in inviting for and empowering integrative and synergetic transformations of knowledge between stakeholders in climate adaptation projects.